Azospirillum griseum sp. nov., isolated from lakewater. Issue 12 (28th May 2019) - Yang, Yunzhen; Zhang, RanRan; Feng, Jie; Wang, Chao; Chen, Jifeng
Abstract : A novel Gram-stain-negative, strictly aerobic, rod-shaped, gray-pigmented bacterial strain, designated L-25–5 w-1 T, was isolated from the water at Baiyang Lake, PR China. Cells of strain L-25–5 w-1 T were motile, with a single polar flagellum. L-25–5 w-1 T was able to grow at 15–37 °C (optimum 37 °C) and pH 5–8 (optimum pH 6) in R2A medium. 16S rRNA gene sequence analysis and phylogenetic analysis of L-25–5 w-1 T showed the highest relationship to Azospirillum doebereinerae GSF71 T (97.9 %), Azospirillum thiophilum DSM 21654 T (97.9 %) and Azospirillum agricola CC-HIH038 T (97.0 %), with other species of the genus Azospirillum showing less than 97 % sequence similarity. The predominant polar lipids were phosphatidylethanolamine, phosphatidylcholine, phosphatidylglycerol, diphosphatidylglycerol and two unidentified aminolipids; the major cellular fatty acids were C16 : 0, C16 : 0 3-OH, C18 : 1 2-OH, iso-C18 : 0, summed feature 2 (C12 : 0 aldehyde and/or unknown 10.9525 and/or iso-C16 : 1 I and/or C14 : 0 3-OH), summed feature 3 (C16 : 1 ω7 c and/or C16 : 1 ω6 c ) and summed feature 8 (C18 : 1 ω7 c and/or C18 : 1 ω6 c ); and the major respiratory quinone was ubiquinone 10. The draft genome size of L-25–5 w-1 T was 5.8 Mbp, and the DNA G+C content was 66.6 %. The average nucleotide identity value and digital DNA–DNA hybridization relatedness value between L-25–5 w-1 T and related type strains were 80.2 and 24.7 % with A. doebereinerae GSF71 T and 78.8 and 23.6 % with A. thiophilum DSM 21654 T, respectively. According to the phylogenetic, chemotaxonomic and genotypic properties, strain L-25–5 w-1 T represents a novel species in the genus Azospirillum, for which the name Azospirillum griseum sp. nov. is proposed. The type strain is L-25–5 w-1 T (=CGMCC 1.13672 T =KCTC 62777 T ).